2012
DOI: 10.3109/00016489.2012.680980
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Meniere's disease from a radiological aspect – saccular otoconia as a cause of Meniere's disease?

Abstract: ConclusionSignificant reduced visualization of the reuniting duct (ductus reuniens; RD), saccular duct (SD) and endolymphatic sinus (ES) in Meniere's disease (MD) compared with normal control ears on three-dimensional (3D) CT imaging suggests the blockage of endolymphatic flow there with radiodense substances, which may be explained by dislodged otoconia from the saccule. These structures could be involved in the pathogenesis of MD.ObjectiveThis study was designed to visualize and assess the RD, SD and ES in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 18 publications
2
28
0
1
Order By: Relevance
“…This difference was most observable for HV thresholds, which reinforces the evidence of predominantly saccular dysfunction in these patients [5, 32]. Second, thresholds were lowest in VM, but not significantly lower than thresholds measured in HC.…”
Section: Discussionsupporting
confidence: 81%
“…This difference was most observable for HV thresholds, which reinforces the evidence of predominantly saccular dysfunction in these patients [5, 32]. Second, thresholds were lowest in VM, but not significantly lower than thresholds measured in HC.…”
Section: Discussionsupporting
confidence: 81%
“…To determine the patency of these ducts, in a previous study we examined whether 3D CT images showed or did not show continuity of the luminal spaces of these ducts (Figure 1) [9]. When luminal spaces on a 3D CT image were totally absent, the ducts were defined as occluded, and any other states were defined as patent.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we used the same subjects as in the previous study [9], to allow comparison with the present study. We classified the 3D CT images of the ducts based on their occlusion patterns to obtain more precise information on MD, and investigated the relationships between pattern and MD stage.…”
Section: Introductionmentioning
confidence: 99%
“…Otoconia: Studies using three-dimensional (3D) computerized tomography (CT) imaging in patients show that hydrops in MD patients might be caused by obstruction of the duct reunions by loose otoconia in the saccule [13].…”
Section: Etiology Of the Hydropsmentioning
confidence: 99%